DAMAGE TO TARGET ORGANS IN ARTERIAL HYPERTENSION (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2026)
Arterial hypertension is one of the most prevalent chronic non-communicable diseases worldwide and a major risk factor for cardiovascular morbidity and mortality. Persistent elevation of blood pressure leads to progressive structural and functional alterations in vital organs, commonly referred to as target organ damage. These organs include the heart, kidneys, brain, retina, and vascular system. Target organ damage often develops silently and may precede overt clinical complications such as myocardial infarction, stroke, heart failure, and chronic kidney disease. This scientific article provides a comprehensive analysis of the mechanisms, manifestations, and clinical significance of target organ damage in arterial hypertension. The paper reviews current literature on hypertensive heart disease, nephropathy, cerebrovascular injury, hypertensive retinopathy, and vascular remodeling. Pathophysiological mechanisms such as endothelial dysfunction, oxidative stress, inflammation, and neurohormonal activation are discussed in detail. The results section presents comparative tables and illustrative figures summarizing clinical indicators of organ damage in hypertensive patients. The article emphasizes the importance of early detection, risk stratification, and integrated management strategies to prevent irreversible organ damage and reduce cardiovascular risk.